Odpowiedzi

2010-02-06T20:17:14+01:00
A) 2(a-3b)-3(a-b)-5(4a+3b) = 2a-6b-3a+3b-20a-15b=-21a-18b

b) -3(2x-3y)+5(x+2y)-2(3y-x)= -6x+9y+5x+10y-6y+2x= x+13y

c) 5(b-2a)+3(a-3b)-4(2a-4b)= 5b-10a+3a-9b-8a+18b = 15b-15a

d) -5(2x+2y-6z)-(x-7y-3z) = -10x-10y+30z-x+7y+3z=-11x-3y+33z

e) 2x(x-3x+7)+3(x-2x+4) = 2x ² - 6x ² +21x + 3x -6x +12 = -4x²+18x+12
2010-02-06T20:18:08+01:00
A)2a-6b -3a+3b - 20a-15b = -21a -18b
b) -6x +9y +5x +10y - 6y +2x = x + 13y
c) 5b - 10a + 3a - 9b - 8a +16b =15b - 15a
d) -10x - 10y + 30z - x+ 7y + 3z = -11x -3y + 33z
e) 2x² - 6x² + 14x + 3x -6x + 12 = -4x² + 11x +12